Dampak Kebijakan Pajak Ekspor Minyak Sawit Mentah (Cpo) Terhadap Kinerja Makroekonomi Dan Sektoral Di Indonesia : Pendekatan Model Keseimbangan Umum - Rustam Abd. Rauf (Universitas Tadulako, 2007)
This reearch intends to analyze the policy impact of export tax evailed for Crued Palm Oil (CPO) on macroeconomic and sectoral performances using export tax simulation through Computable General Equilibrium application. Using 5 scenarios, export tax cause the ratio of balance of trade to GDP declined (delBreal) from -318,84 percent to -190,62 percent. This impact occured as a result of a decrease in export tax responded directly by an increase in export volume and export value. Prevailing high export tax would weaken demand of investment in agriculture sector, particularly in plantation and CPO.